The application of semi-synthetic biopolymer nano-carrier complexes for drugs with low oral bioavailability - Sithole, Mduduzi Nkosinathi (My University, 2016)
The major challenge in pharmaceutical research is the improvement of drug efficacy, including enhancement of solubility and permeability, leading to an improved oral bioavailability of drugs.
A dissertation submitted to the Faculty of Health Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Masters of Science in Medicine University of the Witwatersrand, Department of Pharmacy and Pharmacology, Johannesburg, South Africa 2016